Bilateral phyllodes tumor of the breast in a young nulliparous woman - Soni, Rajesh K.; Sinha, Ajit; Kunal, Abhishek; Anand, Arun (International Journal of Research in Medical Sciences, 2017)
Cystosarcoma phyllodes is a rare breast tumor with incidence of 1% of all the mammary tumors. Bilateral occurrence is very rare. Median age of presentation is 40-50 years. We present a case of 24 years old nulliparous female with phyllodes tumour developing in both the breasts one after another with a gap of five years. Patient underwent simple mastectomy on both sides. Histopathology report confirmed benign variety of cystosarcoma phyllodes on both sides.